The Remodeling Effects of High-Concentrate Diets on Microbial Composition and Function in the Hindgut of Dairy Cows - Zhang, Ruiyang; Liu, Junhua; Jiang, Linshu; Wang, Xinfeng; Mao, Shengyong (Frontiers in Nutrition, 2022)
At present, research on high-concentrate (HC) diets mostly focused on the rumen, and there is a paucity of information on the hindgut microbiota of dairy cows. In the present study, a 2 × 2 crossover design with four healthy Holstein cows were used, and the metagenomics approach was adopted to reveal the remodeling effects of HC diets on hindgut microbiota and their metabolic functions. Results showed that, compared with the low-concentrate diets (LC), HC diets markedly decreased (P < 0.05) the abundance of cellulolytic bacteria (such as Fibrobacter, Ruminococcus, and Ruminiclostridium) and methanogens (such as Methanobrevibacter, Methanosarcina, and Methanosphaera); and correspondingly, HC diets significantly reduced (P < 0.05) the abundance of carbohydrate-active enzymes related to hemicellulases (GH10, GH11 and GH54) and cellulases (GH1, GH44, and GH45) and increased the abundance of one oligosaccharide-degrading enzyme (GH32). Furthermore, 62 KEGG pathways of hindgut microbiota were affected (P < 0.05) by different dietary treatments, and the major pathways altered by HC diets were “Methane metabolism” (enriched in the LC group), “Lipid metabolism” (enriched in the HC group), and several sub-pathways in “Amino acid metabolism” (such as Phenylalanine metabolism, and Phenylalanine, tyrosine and tryptophan biosynthesis). Also, the microbial genes involved in the pathways “Methane metabolism” (except 1 gene), “Tryptophan metabolism” and “Phenylalanine metabolism” were all decreased (P < 0.05) in the present study. These findings suggested that HC diets caused the remodeling of hindgut microbiota and its potential functions, and these results may benefit in gaining a deeper understanding of the impact of HC diets on hindgut microbiota of dairy cows.